Analisis Pengaruh Rasio Keuangan terhadap Harga Saham Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia (BEI Tahun 2011-2013) - Yuliati, Firtia, Zulfa Irawati, S.E., M.Si (2015)
This study aims to find out about the influence of financial ratio on stock price, which independent variables are Return On Asset (X1), Return on Equity (X2), Net Profit Margin (X3) and Earning Per Share (X4) affect the stock price (Y) as the dependent variable. The population in this study is the Automotive Company listed on the Indonesia Stock Exchange in 2011-2013. Samples taken as many as 48 by using purposive sampling. Data were analyzed using multiple regression analysis. Other analyzes include Classical Assumption Test, Hypothesis through F test and t test, and analysis of the coefficient of determination (R2). Based on the analysis of data in the discussions can be concluded that the ROA, ROE and EPS have a significant effect on stock price. While NPM variable has no significant effect on stock price. But the results of the F test analysis shows that ROA, ROE, NPM, and EPS, together have a significant effect on stock price. In addition ROA, ROE, NPM, and EPS can explain stock price at Automotive Company Listed on the Stock Exchange of 42.5%, while the remaining 57.5% can be explained by other variables outside the model. Keywords: Return on Assets, Return on Equity, Net Profit Margin, Earnings Per Share, Price Stock.